PENGARUH PEMEKARAN WILAYAH TERHADAP PERTUMBUHAN PDRB PER KAPITA (STUDI KABUPATEN SIJUNJUNG) - RAMADHAN, KHAIRUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study aims to: (1) determine effect of the regional expansion to the GDP growth rate during the year 1994-2013 in the Sijunjung District, (2) determine effect of the regional expansion to the GDP per capita rate during the year 1994-2013 in the Sijunjung District, (3) determine effect of the regional expansion to the economic base during the year 2000-2013 in the Sijunjung District and Dharmasraya District. This research was conducted by analyzing the GDP tables District Sijunjung Year 1994-2013. This new analysis is the rate of growth in GDP and sector basis Sijunjung district. Furthermore, this study analyzes the influence of regional divisions with, t test of equal mean and Location Quotient (LQ) index. The analysis showed significant differences have occurred GDP growth rate and GDP per capita in the Sijunjung District after expansion during the period 1994- 2013. There was also an increase in the base sector parent after separation, while New Autonomous Region (DOB) remains. At the base of the origin region sector prior to the division by 4 sectors, namely agriculture, mining and quarrying, construction, the service sector - services. After expansion the sector into a master database on the 5 sectors, namely agriculture, mining and quarrying, electricity, gas and water supply, construction, the services sector. On the basis of sector DOB prior to the division by 4 sectors, namely agriculture, mining and quarrying, construction, the service sector - services. After expansion the base sector remains DOB 5 sectors, namely agriculture, mining and quarrying, construction, the services sector.